Optimal destabilization of cartels - Ludwig von Auer; Tu Anh Pham (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2019)
The literature on cartel stability sidelines antitrust policy, whereas the literature on antitrust policy tends to neglect issues of cartel stability. This paper attempts to connect these two interrelated aspects in the context of an augmented quantity leadership model. The cartel is the Stackelberg quantity leader and the fringe firms are in Cournot competition with respect to the residual demand. The antitrust authority decides on its own investigative effort and on the size of the fine that cartel members have to pay when they are detected. For testifying cartel members a leniency program is implemented. Our framework takes into account that these antitrust policy instruments are not costless for society. Our model demonstrates that the optimal antitrust policy exploits the inherent instability of a cartel to reduce its size.
Keywords: L13; L41; 330; antitrust; stability; Cournot fringe; oligopoly; leniency